Intensifying the use of benefit sanctions: an effective tool to shorten welfare receipt and speed up transitions to employment? - Bernhard Boockmann; Stephan L. Thomsen; Thomas Walter (Institute for the Study of Labor (IZA), 2009)
Benefit sanctions imposed on non-compliant welfare recipients are a new element in the German welfare system. In practice, the sanction policy and the application of sanctions vary considerably across the 439 welfare agencies. Based on combined administrative and survey data, these differences are used as instrumental variables to estimate the effect of sanctions on the drop-out from welfare and the transition to employment. The estimated local average treatment effect (LATE) is an estimate of the effectiveness of an intensified use of sanctions. The results show that tightening sanction policy would be quite effective.
Keywords: I38; J64; C31; 330; Benefit sanctions; welfare recipients; IV; LATE; Sozialhilfeempfänger; Hartz-Reform; Rechtsdurchsetzung; Wirkungsanalyse; Arbeitsuche; Berufliche Integration; Deutschland